FORMS OF SUSTAINABLE TOURISM SUITABLE TO APUSENI MOUNTAINS, ROMANIA - Bac Dorin Paul (Annals of the University of Oradea: Economic Science, 2015)
Sustainable tourism is the result of the melange between tourism and sustainable tourism. The concept has evolved during the last decades of the twentieth century, in international conferences, summits etc. organized by the World Tourism Organization, the United Nations and other international organizations where it was defined, characterized and criticized. Unfortunately, the concept was not able to overcome its theoretical conceptualization and it did not reach practitioners of the tourism industry. Sustainable tourism has several forms which are actually practiced by tourists all over the world: ecotourism, backpacking, rural tourism, nature-based tourism, pro-poor tourism, volunteer tourism etc. In the present paper, we have focused on an area in Apuseni Mountains, Romania. We tried to identify the forms of sustainable tourism most suitable for this area considering: natural resources, socio-economical development, protected areas, gastronomic traditions etc. After considering all these we have selected three forms: ecotourism, volunteer tourism and slow tourism, which could have the highest impact in promoting this area, and actually all the Apuseni Mountains as an important destination for sustainable tourism. The arguments for ecotourism are based on the numerous natural tourism resources> caves, gorges, forests and wildlife. Volunteers are needed especially in conservation and English language course. For slow tourism, there are numerous trails for walking and biking. Also there are several foods, mainly based on milk and wild berries that should be promoted and sold under the slow food brand. The shortcomings of the research are the lack of quantitative and qualitative results, as there is no information regarding the number of tourists which visit the area during each year. Also, it is hard to compare the benefits of sustainable tourism with those of mass tourism, due to the lack of references. So it is harder to argue for sustainable tourism and its forms to the detriment of mass tourism.